2009
DOI: 10.1097/aog.0b013e3181ac3e03
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intraoperative Capsule Rupture on Outcomes in Stage I Epithelial Ovarian Cancer

Abstract: OBJECTIVE:To evaluate the effect of tumor capsule rupture on disease prognosis in stage I epithelial ovarian cancer. METHODS: All patients with International Federation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This increases the risk of spilling cyst fluid containing malignant cells into the peritoneal cavity (44). Previous studies clearly showed that rupture of a malignant ovarian cyst worsens the prognosis for diseasefree survival in stage I invasive ovarian cancers (2,3). Spilling should also probably be avoided in borderline tumors, even though there are no prospective studies to prove this (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the risk of spilling cyst fluid containing malignant cells into the peritoneal cavity (44). Previous studies clearly showed that rupture of a malignant ovarian cyst worsens the prognosis for diseasefree survival in stage I invasive ovarian cancers (2,3). Spilling should also probably be avoided in borderline tumors, even though there are no prospective studies to prove this (44).…”
Section: Discussionmentioning
confidence: 99%
“…Benign masses can be managed conservatively or-if technically feasible-be removed by laparoscopy. However, patients with masses that are presumed to be malignant should be referred to gynecologic oncologists for proper staging and debulking (1)(2)(3). A mistake in either direction could worsen the patient's prognosis or create unnecessary anxiety, cost, and extensive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative tumor spill is also taken as IC disease even when the tumor is confined to one ovary according to FIGO staging and hence all attempts should be made during surgery to deliver the tumor without spillage. There is varying reports on the risk of tumor spillage on patient survival, some authors reporting poorer survival after tumor spillage, while others contradicting the same [13][14][15][16].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…However, cystic rupture and spillage occurred in 121 cases [32]. The implications of a ruptured benign cyst are negligible, but rupture of a stage I ovarian malignancy results in an increase in stage and may lead to a worse disease-free survival [33].…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%